GRAVITATIONAL LENSING EFFECTS ON IMAGE OF DISTANT OBJECT - Hassan, Sundus D (Al-Nahrain Journal of Science, 2009)
This paper present studying the effect of gravitational lensing on magnification factor and the location of image for distant object (quasar).We assume the lens to be point mass lens. The cosmological parameters are represent by mathematical equations and programmed by mat lab language to compute these parameters .The results show the mass lens a great effect on the image position magnification and agreement with other models.